Hepatoprotective effect of essential phospholipids enriched with virgin coconut oil (Phoscoliv) on paracetamol‐induced liver toxicity. Issue 2 (17th January 2021) - Sreevallabhan, Sheethal; Mohanan, Ratheesh; Jose, Svenia P.; Sukumaran, Sandya; Jagmag, Tariq; Tilwani, Jayesh; Kulkarni, Anuradha
Abstract: The prevalence of liver disease is increasing year by year and it is recognized as a main health burden across the world. Nowadays, dietary nutraceuticals are found to be very effective in the prevention and treatment of liver diseases. The virgin coconut oil and phosphatidylcholine are found to have a wide range of therapeutic efficacy and the most important among them is its hepatoprotective activity. In the present study, we had evaluated the hepatoprotective effect of the novel formulation with the combination of these two which is named as Phoscoliv. For the study, adult Wistar rats were grouped into Normal control, Paracetamol‐treated, and Paracetamol along with Phoscoliv‐treated group. In order to evaluate the hepatoprotective effect of the drug, various parameters were analyzed. Data obtained from the study showed that Phoscoliv supplementation were found to significantly boost up the antioxidant status by enhancing the SOD, CAT, GPx, and GSH level and thereby inhibit the generation of ROS and also blocked lipid peroxidation, which was confirmed by the reduced level of TBARS. The release of pro‐inflammatory cytokines was also decreased, which was eventually helped to maintain the normal architecture of the liver. Thus, from the overall result of this study reveals that Phoscoliv can be effectively used as a potent and safe hepatoprotective medicine. Practical applications: The over or unwanted usage of synthetic medicine is a serious problem because it can cause so many adverse health effects. Liver‐related disorders are the major side effects of these drugs. Food habits of ancient people dictate that there is no other better medicine than a good food. So, treating a disease with a food or compounds derived from a food item will be more effective. Virgin coconut oil is a type of natural and organic oil, which has the capability of maintaining the body in a healthy state. Likewise, phosphatidylcholines are very important phospholipid nutrients necessary to keep the cells healthy. Both these have the potential to protect and prevent the liver damages. Therefore, the combination of these two can exhibit profound hepatoprotective activity. Abstract : Paracetamol is considered as one of the common reasons for drug‐induced hepatotoxicity. Over dosage of this drug causes the accumulation of its toxic metabolites which reduces the antioxidant status and increases the free radicals that induce lipid peroxidation, mitochondrial damage, and release of inflammatory cytokines which ultimately lead to hepatocellular damage. Supplementation of Phoscoliv will help to detoxify the accumulated toxic metabolites by enhancing antioxidants thereby, prevent the other destructive processes triggered by ROS and thus, maintain the liver healthier.